Characterization of fowl adenoviruses isolated from field outbreaks of hydropericardium syndrome in Punjab - SINGH, AMARJIT; KUMARI, ANUPAMA; MAITI, N K; OBEROI, M S (The Indian Journal of Animal Sciences, 2014)
Fowl adenovirus (FAV) isolates (LHPSV-2, 4, 6 and 7) obtained from field outbreaks of hydropcricardium syndrome (HPS) were characterized as serotype-4 of FAV using virus neutralization test. The pathogenicity of isolate LHPSY -7 wasstudied in experimental birds. Clinical disease appeared on 3 days post inoculation (DPI) of HPS isolate (LHPSV-7) in 3-week-old disease free broiler chicks. In experimental birds 16.8% mortality was observed. The severity of disease wasseen between 5 and 7 DPI. The dead and sacrificed birds showed characteristic hydropericardium with transparent, amber coloured fluid in the pericardial cavity. Characteristic pathological changes in liver included, necrotic hepatitis andintranuclear inclusion bodies in hepatocytes. The inclusions were also observed in kidneys, heart, spleen and pancreas atvariable stages of infection. Microscopically, depletion of lymphoid cells was observed in bursa, thymus, spleen and caecal tonsils. FAY antigen was detected at 7,13 and 21 DPI in plasma by antigen capture ELISA. Antibodies to FAV weredetected in serum by AGPT and indirect ELISA from 7 DPI onwards. A high titre (GMT> 1:64) was seen first on 3 DPIfollowed by a dcerease in antibody titre, which again increased by 21 DPI (GMT> 1:53.81).